The Effectiveness of Hyperbaric Oxygen Therapy in an Established Intracerebral Tumor Model - DÜNDAR, TOLGA TURAN; DÜNDAR, TOLGA TURAN; SEYİTHANOĞLU, MEHMET HAKAN; SEYİTHANOĞLU, MEHMET HAKAN; KORPINAR, ŞEFİKA; ATAR, RAZİYE; EVRAN, ŞEVKET (My University, 2015)
Objective: Gliomas are the most common brain tumor in adults. Tumor-related endothelial cells are of neoplastic nature and have malignant properties such as proliferation and invasion. Therefore, antiangiogenic approaches have several advantages compared with conventional chemotherapeutic approaches. The target of antiangiogenic treatment is to ensure a decrease in systemic side effects because there are endothelial cells and other supportive cells belonging to the vessel walls. The purpose of this study was to increase the oxygenation of the environment with hyperbaric oxygen therapy (HBOT) and to prevent the angiogenic effect of hypoxia- related factors. We also tried to prevent angiogenesis by using sorafenib (SOR), which is a chemotherapeutic agent that blocks the receptors of these factors. Also, this study compared the effect of these both and to put into for their effect. In this regard, parameters such as the tumor size, vascularization rate, midkine (MK), apoptosis- and angiogenesis-related transcription tumor necrosis factor (TNF) alfa, and IL6 were compared in the relevant groups. Methods: For this purpose, a convenient trial model was formed and the following 4 groups were determined: The study population was divided into four main groups: G1-control group, G2-group given HBOT, G3-group given SOR, G4-group given HBOT and SOR. Ten rats were included in each group. After 2 weeks, the rats were sacrificed. After being sacrificed based on the date and surgery determined, the tumor volume and vascularization ratio were checked with light microscope. Serum samples are evaluated by using ELISA for TNF-alpha, Interleukin-6 (IL- 6) and midkine (MK) levels. Results: The underlying mechanism of HBOT by evaluating MK levels was shown for the first time in this study. We have found that HBOT potentializes the sorafenib efficacy. HBOT increased MK levels and HBOT decreased anti-apoptotic TNF-α and IL-6 levels. MK levels show inverse correlation with TNF-α levels and IL-6 levels. TNF-α and IL-6 levels are directly proportional. Conclusion: There is a need for further studies to evaluate the correct time of application of HBOT.
Keywords: HBOT